A origem de populações emergentes do patógeno da queima-da-folha (Rhizoctonia solani AG-1 IA) da Urochloa spp. na Amazônia e seu potencial de adaptação a outros agroecossistemas brasileiros - Chavarro Mesa, Edisson [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The fungus Rhizoctonia solani AG-1 IA emerged in the early 1990s as an important pathogen causing leaf blight and collar rot on pastures of the genus Urochloa (signalgrass) in South America. This pathogen first emerged in Colombia in areas where rice, a host highly susceptible to the fungus, was replaced with Urochloa in response to increased demand for extensive livestock farming. Urochloa is an extremely important forage grass crop for livestock farming in tropical Latin America. Described in the first part of our study, a broad survey was conducted in the Amazon in Pará, Rondônia, Roraima states and in Mato Grosso Cerrado areas, and paddy plains in the Paraíba Valley, in São Paulo, between 2012 and 2013. Our findings revealed that R. solani AG-1 IA was the predominant pathogen associated with the leaf blight on Urochloa in the Brazilian Amazon biome, especially in Rondônia. In the second part of our study, describing the population genetic structure of different host and regional populations of R. solani AG-1 IA infecting Urochloa, rice and soybean, we tested the hypothesis that the emergence of this pathogen occurred due to host shift or jump as a result of geographical overlapping of the host species. To study the genetic structure of populations, a total of 335 R. solani AG-1 IA isolates were sampled from fields of U. brizantha, Urochloa hybrid Mulato, rice and soybeans in Colombia and Brazil. These isolates were genotyped using nine microsatellite loci. The historical patterns of migration of populations from different hosts indicated that the populations currently infecting Urochloa in Colombia most likely originated from a population that originally infected rice. In contrast, in Brazil a similar clear asymmetric pattern of historical migration was not established because the migration rates among Brazilian R. solani AG-1 IA populations from Urochloa, soybean and rice were all symmetric in magnitude (average 20 migrants ...

No início dos anos 90, o fungo Rhizoctonia solani AG-1 IA emergiu como um patógeno importante associado à queima foliar e podridão do coleto em pastagens do gênero braquiária (Urochloa spp.), na América do Sul. Este fungo surgiu pela primeira vez na Colômbia em áreas onde o cultivo de arroz (um hospedeiro altamente suscetível ao fungo) foi substituído por Urochloa, em resposta ao aumento da demanda por pecuária extensiva. Urochloa é uma forrageira de extrema importância para a pecuária da América Latina tropical. Descrito na primeira parte de nosso estudo, um amplo levantamento foi realizado na Amazônia nos estados do Pará, Rondônia, Roraima, e nos Cerrados de Mato Grosso e em áreas de várzeas do Vale do Paraíba, em São Paulo, entre 2012 e 2013. Nossas descobertas revelaram que Rhizoctonia solani AG-1 IA predominou como patógeno associado à queima-da-folha da braquiária no bioma Amazônico Brasileiro, especialmente em Rondônia. Na segunda parte de nosso estudo, descrevendo a estrutura genética de populações de R. solani AG-1 IA que infectam braquiária, arroz ou soja, testou-se a hipótese de que a emergência desse patógeno ocorreu devido a troca ou pulo de hospedeiros, dada a sobreposição geográfica de espécies hospedeiras. Para estudar a estrutura genética das populações, um total de 335 isolados de R. solani AG-1 IA foram coletados de campos de U. brizantha, de Urochloa híbrido Mulato, de arroz ou de soja, na Colômbia ou no Brasil. Esses isolados foram genotipados usando nove loci microssatélites. Padrões históricos de migração entre populações hospedeiro-distintas indicaram a origem provável das populações atuais que infectam braquiária na Colômbia, a partir de população que originalmente infectava o arroz. No Brasil, em contraste, não foi possível estabelecer o mesmo padrão claro assimétrico de migração histórica, uma vez que a migração entre as populações brasileiras de...
Keywords: Pastagens; Fungos fitopatogenicos; Adaptação (Biologia); Enzimas; Genetica de populações; Enzymes